COMPARATIVE ANTIMICROBIAL SCREENING OF SATVA (SEDIMENTED STARCHY AQUEOUS EXTRACT) AND GHANA (SOLIDIFIED AQUEOUS EXTRACT) OF GUDUCHI (TINOSPORA CORDIFOLIA (WILLD.) MIERS) - Sharma, Rohit (Innovare Journal of Ayurvedic Sciences, 2017)
Abstract: Guduchi (Tinospora cordifolia (Willd.) Miers) is incredibly versatile vine in ayurvedic system of medicine since ancient times and is indicated for potential use in wide range of diseases. Recent reports investigated and ascertained its role as a potent antimicrobial herb. Guduchi Satva and Ghana are popularly known formulations in ayurvedic fraternity for their huge therapeutic credentials. However, no published reports on comparative antimicrobial profile of Guduchi Satva and Ghana are available. Present study was therefore attempted to evaluate comparative antimicrobial efficacies of these two dosage forms of Guduchi: Satva and Ghana. Recommended microbial strain like; Salmonella typhi, Escherichia coli, P. aeruginosa and Staphylococcus aureus were used in this study for the same purpose. Both samples showed significant antibacterial activity and possess great potential against microorganisms. Phytochemical analysis for various functional groups revealed the presence of glycosides, alkaloids, tannins, phenols, starch and sterols in GG, while presence of only alkaloids and starch in GS., which suggests the alkaloidal contentsÂ might be accountable for their antimicrobial potential. No microbial load was detected within both samples. The results also validate the traditional uses of Guduchi in various skin ailments and infectious disorders. Present study may prove a torch bearer for future studies to understand its biological activities. Keywords: Antimicrobial activity, Guduchi, Guduchi Ghana, Physicochemical, Tinospora cordifolia